Pengembangan Sumber Daya Manusia di Puskesmas Kabupaten Langkat Kecamatan Salapian - Harahap, Farida Hanim; Siregar, Helmi Zahra; Selian, Liza Syintani Putri; Panjaitan, Umaimah Zahroh; Lestari, Winda Sri; Oktami, Rida; Gurning, Fitriani Pramita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The World Health Organization (2006) reported that healthcare workers contribute up to 80% to the success of health development, and one of the best ways to address the healthcare crisis is through training and improving human resource management. Human resource development is an effort to enhance the quality or capacity of human resources through the process of education planning, training, and improving human resource management policies. Healthcare workers are essential for health services, so leaders must consider all their needs, desires, and interests in order to work at their best. To determine the development of human resources in Langkat District, Salapian Subdistrict, this research uses qualitative research. Primary data collection was conducted through in-depth interviews (departmental interviews). Information obtained from in-depth interviews with informants was processed and analyzed using content analysis methods. The types of healthcare workers in Langkat District, Salapian Subdistrict, consist of Health Human Resources (SDMK) which are still dominated by medical personnel, including 7% dental doctors, 11.2% general practitioners, 45% midwives, 21.1% nurses, Meanwhile, public health workers are 5.6%, environmental health workers are 2.8%, pharmaceutical workers are 4.2%, nutrition health workers are 1.4%, and medical laboratory technology experts are 1.4%. The development of SDMK is in accordance with the standards for demand development. The acquisition of human resource development training is limited to medical personnel and its distribution is still uneven.